The Model of Technology Management in Digital Era of School Administrators under Narathiwat Primary Educational Service Area Office 2 - Cheknooh, Padelee; เก้าเอี้ยน, จรุณี; สุวรรณโณ, พิมพ์ปวีณ์ (Al-HIKMAH Journal, 2024)
Technology management in digital era of school administrators under Narathiwat Primary Educational Service Area Office 2, and 2) create the model of technology management in digital era of school administrators under Narathiwat Primary Educational Service Area Office 2. The research process consisted of two steps. Step 1: to examine the documents and research related to technology management in digital era of school administrators in order to obtain interview topics and qualitative data collection, using semi-structure interviews with 11 were conducted. The data was analyzed by using content analysis to create a conceptual framework and outline the draft model of technology management in digital era of school administrators. Step 2: submitting the draft model of technology management in digital era to three qualified experts for validation and content validity assessment were processed. The index of item objective congruence (IOC) of three experts ranged from 0.67 to 1.00 with a confidence level of .992. Once validated, the model of technology management in digital era was applied to a sample group of 348 individuals, and data analysis was conducted using statistical software package to calculate means and standard deviations. The results revealed that: Phase 1: The condition and model of technology management in digital era of school administrators under Narathiwat Primary Educational Service Area Office 2 consisted of four characteristics involving 1) teaching and learning management, 2) management within the educational institution, 3) measuring and evaluating learning outcomes, and 4) infrastructure. Phase 2: The model of technology management in digital era of school administrators under Narathiwat Primary Educational Service Area Office 2 consisted of four characteristics: 1. Teaching and learning management included 1) school administrators supported the use of technology in digital era among staff or teachers, 2) school administrators promoted the use of material or innovative teaching and learning aligning with education management in digital era, and 3) school administrators promoted technology in digital era to develop learners integrating education management with community lifestyles. 2. Management within the educational institution included 1) school administrators clearly designated individuals to be responsible for technology in digital era, 2) school administrators promoted the use of information and communication technology according to teachers’ opinions, and 3) school administrators utilized technology in digital era as a tool for school management. 3. Measuring and evaluating learning outcomes included 1) school administrators clearly set calendars for learning management assessment and evaluation, 2) school administrators used technology in digital era to develop assessment and evaluation systems in learning management within the school clearly, and 3) school administrators adapted assessment and evaluation formats for learning management in the digital era appropriately. 4. Infrastructure included 1) school administrators reinforced rewards and encouragement, 2) school administrators showed vision, attitudes, managed the environment, and prioritized reinforcement, and 3) school administrators managed accessing any school information for staff and the community.